Profiles of African American College Students' Alcohol Use and Sexual Behaviors: Associations With Stress, Racial Discrimination, and Social Support. - Metzger, Isha W; Cooper, Shauna M; Ritchwood, Tiarney D; Onyeuku, Chisom; Griffin, Charity Brown (Journal of sex research, 2016)
Though studies show that alcohol use and sexual activity increase during emerging adulthood, few studies examine within-ethnic group differences, particularly among African American college students. This investigation utilized a latent class analytic methodology to identify risk behavior profiles of alcohol use (frequency and amount of alcohol consumed), sexual activity (number of intimate partners), and co-occurring risk behaviors (drinking before sexual intercourse) among 228 African American college students. This investigation also examined whether identified risk behavior profiles were associated with stress (interpersonal, intrapersonal, academic, and environmental), experiences of racial discrimination, and social support (from family, friends, and the college community). Results identified five distinct profiles within this sample: (a) High Sexual Risk-above-average sexual activity; (b) Abstainers-below-average alcohol use and sexual activity; (c) Low Risk-average alcohol use and sexual activity; (d) Alcohol Risk-above-average alcohol use and below-average sexual activity; and (e) Co-Occurring Risk-above-average alcohol use and sexual activity. Identified profiles differed across interpersonal and environmental stress, and self-reported frequency of experiences with racial discrimination. Implications for prevention programs and interventions aimed at reducing alcohol and sexual activity for African American college students are discussed.